Adherence prediction between ribbed steel rebars and concrete: A new perspective and comparison with codes. (June 2020) - Biscaia, Hugo C.; Soares, Sérgio
Abstract: The interfacial behaviour between ribbed steel rebars and concrete has been extensively studied because the contribution of the adherence between these two materials is of the utmost importance for the behaviour of Reinforced Concrete (RC) structures. The majority of the available studies on this topic indicate that the local adherence between these two materials can be defined through a bond-slip relationship, which is obtained with short embedded lengths. Although this seems to be widely accepted, some incoherencies, mainly regarding the local and the global detachment process in that "conventional theory", are identified in the present work. To facilitate the understanding of the detachment process between a ribbed steel rebar and concrete, an analytical solution is developed. An experimental program with 33 pull-out tests covering three different ribbed steel rebars with different diameters and embedded lengths was carried out. Based on the experimental load–displacement at the pulled end responses, a new local bond-slip relationship with friction is proposed. In the end, the new bond-slip relationship, as well as other known relationships, is implemented into a Finite Element (FE) commercial code and the results are compared to the experimental data. Based on these preliminary results and up to the yielding point of the steel rebars, the new proposed local bond-slip model is the only one able to clearly distinguish and simulate either the local and the global performances of the tested specimens.